IOT PRISON BREAK MONITERING AND ALERTING SYSTEM (International Journal of Food and Nutritional Sciences, 2021)
We have surveillance systems for protection of public places such as banks, shopping malls, homes, etc. from robbers, and other negative people. People are well acquainted with current security systems of the Indian jails. There are some system like CCTVs, drones and guards are used to monitor the activities of the jail, But as these security systems are not sufficient to monitor all such criminal activity and surely ensure that there is no such chance of the escaping of these prisoners from the prison. There are also many problems associated with the modern security systems, Some of them which are detected issues with these CCTVs are that: not having proper clear images at night, unsaturated camera footage, disturbing videos, visible horizontal lines on videos, no video signal is available sometime, recording system is not their by DVR, starting some false alarms with not proper cause, bright spots on the monitor, etc. By These troubles there are the situation that can be created in the jails where prisoner can get a chance to flee as well as can cause any unexpected activities inside the jail, also deployment of these techniques is quite costlier. Because of this all issue it shows that there is a demand of proper secure security system, that is under budget to use and can provide satisfactory surveillance security solution to the Indian jails also to the society. Many systems are introduced before have to fulfill this demand that generally use equipment such as Iot , Bluetooth, GSM, GPS but these systems are not steady and can be affected by cyber-attacks, which will be the issue of the safety. Now we cameup with this project with an idea to design an advanced and reliable , safe fix for this problem of this situation. Motive behind our device is to implement an safe and monitored environment in the prison that supervise the motion of the prisoners and the outsiders and overcome the problem present with the security modules available in the market previously